2002
DOI: 10.1002/1522-2683(200209)23:17<2833::aid-elps2833>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Semi-empirical relationships between effective mobility, charge, and molecular weight of pharmaceuticals by pressure-assisted capillary electrophoresis: Applications in drug discovery

Abstract: Relationships between effective mobility (m(eff)), calculated charge (Z(c)), and molecular weight (MW) are semi-empirically derived for pharmaceuticals using pressure-assisted capillary electrophoresis (PACE). We determined the m(eff) at 12 different pH points (2.0-11.4) of 66 pharmaceutical-like compounds ranging in MW from 79 to 825 g/mol. Plots of the observed m(eff) values versus Z(c)/MW(x ) (where x is a fractional coefficient) gave linear relationships. For anions, it was found that the best correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The molecular weight (MW) of the compound was entered into the software and the compound charge (Z c ) was estimated by the software using a previously described empirical relationship between MW, maximum m eff and Z c . 28 From the calculated compound charge, a suitable equation from a set of nine different model equations representing up to three ionizable groups 28,22 was selected by the software to perform a nonlinear regression analysis on the data. When performing a cosolvent experiment, the final result is the apparent s w pK a (I ¼ 50 mM) at the particular % methanol concentration.…”
Section: Pk a Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The molecular weight (MW) of the compound was entered into the software and the compound charge (Z c ) was estimated by the software using a previously described empirical relationship between MW, maximum m eff and Z c . 28 From the calculated compound charge, a suitable equation from a set of nine different model equations representing up to three ionizable groups 28,22 was selected by the software to perform a nonlinear regression analysis on the data. When performing a cosolvent experiment, the final result is the apparent s w pK a (I ¼ 50 mM) at the particular % methanol concentration.…”
Section: Pk a Measurementsmentioning
confidence: 99%
“…28 In the case of methotrexate, a predicted charge of þ0.95 and À1.76 indicated that the compound was a monobase/diacid with three pK a values. Similarly, three pK a values were reported by Miller et al 28 using the aforementioned empirical relationship and by Bergström et al 62 using UV spectrophotometry. However, only two pK a values were reported by Wan et al 43 using CE-MS and 10 widely spaced pH buffers.…”
Section: Resolution Of Closely Spaced Pk a Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed literature survey showed that, in recent years many papers have been reported, that have showed the development of many higher throughput methods to determine lipophilicity in industries as there are many novel compounds synthesized [9][10][11]. Also, a large number of data base is available for the determination of log P values by different calculation methods [12].…”
Section: Introductionmentioning
confidence: 99%